Music Cognition and Affect in the Design of Technology-Enhanced Music Lessons - Macrides, Elena; Angeli, Charoula (Frontiers in Education, 2020)
The present study addresses the lack of an instructional design methodology for the integration of technology in music teaching and learning, and explores, within the framework of Technological Pedagogical Content Knowledge (TPCK), the importance of affect in instructional design. The study extends the theoretical framework of TPCK to a design framework and proposes a methodology and instructional design guidelines that address both the cognitive and the affective domains of learning. The research has both practical and theoretical significance as it provides teachers with explicit guidance on how to design music lessons based on TPCK principles, and, examines interactions among content, technology, cognition, and affect. Through the 4E perspective, technology and the proposed approach are viewed as agents of a distributed system that can support the embodied minds to develop musical and emotional understanding.